2021
DOI: 10.3389/feart.2021.705691
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Nitrogen Isotope Profiles in Petroleum Systems: A Review

Abstract: Bulk sedimentary nitrogen isotope profiles are often used as proxies for depositional redox conditions, nitrogen cycling, and nutrient uptake in modern and ancient marine systems. The general preference in terms of analysis is that the sediments measured have undergone minimal thermal alteration, as post-depositional processes might have altered the initial δ15N signal, thus complicating the interpretation of these records. Although not a traditional proxy for petroleum evaluation purposes, recently the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…In addition, the relationship between δ 15 N oil and δ 15 N kerogen during hydrocarbon generation has rarely been reported. 22 Studies on crude oil and kerogen from Liaohe and Tarim found that the δ 15 N of crude oil was comparable to that of the corresponding kerogen. Williams et al 25 also reported that the δ 15 N of crude oil and soluble extracts of source rocks are similar at close reservoir distances 25 so the δ 15 N oil may be expected to become a new oil-source comparative analysis index.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the relationship between δ 15 N oil and δ 15 N kerogen during hydrocarbon generation has rarely been reported. 22 Studies on crude oil and kerogen from Liaohe and Tarim found that the δ 15 N of crude oil was comparable to that of the corresponding kerogen. Williams et al 25 also reported that the δ 15 N of crude oil and soluble extracts of source rocks are similar at close reservoir distances 25 so the δ 15 N oil may be expected to become a new oil-source comparative analysis index.…”
Section: Introductionmentioning
confidence: 99%
“…7,32 Although the loss of nitrogen during diagenesis and catagenesis has been well documented, how these processes alter the δ 15 N signal in different nitrogen-containing compounds has not been determined. 22 Several bulk rock studies have documented an increase in C/N ratios and δ 15 N values with increasing metamorphic grade, 1,33,34 although to varying degrees and not under all circumstances. 35−37 In most cases, the net isotopic effect is on the order of 1−2‰ up to the greenschist facies, but it is often greater at higher metamorphic grades.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations